Stories of People Who Have Attended a Lesbian, Gay, Bisexual and Trans Support Group in a Secure Intellectual Disability Service. Issue 1 (31st August 2016) - Tallentire, Liz; Smith, Matthew; David, Lee; Roberts, Adam; Bruce,; Morrow, Sarah; Withers, Paul; Smith, Ian
Abstract : Background: This research is about people who have intellectual disabilities and live in a secure hospital. It is about a group of people who meet at a support group. The support group is for people who are lesbian, gay, bisexual or transgender. Methods: These people with intellectual disabilities helped with planning, doing, and telling other people about the research. They told their stories about going to the support group. Results: Their stories were joined together into a group story. The story said that the group helped people in lots of different ways. For some people going to the group was difficult at first because it was ?coming out'. This means telling other people you are lesbian, gay, bisexual, or transgender. Then it got easier and people started to feel better about themselves. Then they wanted to help others and this was important in their lives. Conclusions: This group seemed to help people get better. We have given some ideas for setting up other groups and doing more research.